Pendampingan Kader dalam Deteksi Dini dan Edukasi CERDIK sebagai Upaya Pengendalian Penyakit Tidak Menular (PTM) - Mardiyah, Adiyati; Mareti, Silvia; Azmy, Restu Amalia; Zulkifli, Zulkifli; Maktum, Ummi (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
Indonesia is currently facing a double burden of disease, namely infectious diseases (infectious diseases) and non-communicable diseases (degenerative diseases), which are increasing. Currently, non- communicable diseases (NCDs) have replaced infectious diseases as the dominant disease and are the cause of higher deaths compared to infectious diseases. That there has been an increase in key NCD indicators. The increase in cases of non-communicable diseases (NCDs) will significantly increase the burden on society and the government, because handling them requires a long time, large costs and high technology. PTM cases are not transmitted, but they are deadly and cause individuals to become unproductive or less productive. NCDs can be prevented by controlling risk factors through early detection. One of the government's efforts is the CERDIK program to control Non-Communicable Diseases (NCDs). This program is implemented to prevent deaths due to non-communicable diseases by emphasizing promotive and preventive aspects. Based on the background above, this activity aims to support government programs in efforts to control NCDs by assisting cadres in early detection and smart education as part of controlling NCDs. Training activities are carried out by providing demonstrations and teaching how to do early detection related to screening, measuring vital signs, checking body weight, height, body mass index, checking blood sugar, cholesterol and uric acid. Apart from that, cadres are also given clever education regarding controlling non-communicable diseases. The results of the evaluation that have been carried out are that the majority of cadres are in the good category regarding knowledge and attitudes in early detection of PTM.